DATA LOGGER DEBIT AIR DENGAN PROTOKOL M-BUS UNTUK APLIKASI CHILLER - Muhamad Anda Falahuddin; Muhammad Arman; Susilawati S; Wirenda Sekar Ayu (Jurnal Teknologi Terapan, 2023)
The M-bus protocol is one of the communication protocols in the rapidly developing field of measurement. The protocol uses a pair of cables and can communicate with several measurement devices in two directions such as a flowmeter. In the chiller system, water circulation varies depending on the cooling load and set point of operation, consumption (electric power) and chiller efficiency, one of which can be calculated based on logging the flow of water that circulates over time, therefore the water discharge data logger becomes very important. This study aims to examine the water discharge data logger with the M-Bus protocol for chiller applications. The testing device includes a series of bench water meters as flowmeters (which water can be simulated circulated) equipped with an M-Bus pick-up sensor, M-Bus concentrator and logger, and software connected to a computer. Tests carried out with variations in water discharge based on the valve opening as a simulation of cooling load variations and see the results of recording from time to time on a computer. The display can be in the form of tables and graphs.